Enhancing Hydrogen Production Efficiency in Water Electrolysis through Polycarbonate Integration from CD-R Waste - Matthews Romagnoli; Boiral Lymberopoulos Sevastya; Vanechka Valery (Vertex, 2023)
This research explores the integration of polycarbonate derived from CD-R (Compact Disc-Recordable) waste into water electrolysis for hydrogen production, aiming to assess its catalytic potential and influence on electrolysis efficiency. The study investigates the effects of waste-derived polycarbonate on hydrogen evolution rates, electrolysis kinetics, and operational parameters. Experimental trials reveal a notable enhancement in hydrogen production rates with the incorporation of waste-derived polycarbonate, suggesting its potential catalytic influence within the electrolysis process. However, observed variations and nonlinear concentration-efficiency relationships underscore the complexities and challenges in achieving consistent performance. Limitations related to material dispersion and compatibility highlight critical areas requiring optimization for practical implementation. The findings offer insights into the nuances of waste-derived material integration in electrochemical systems, emphasizing the need for further research to address challenges and optimize the utilization of waste-derived materials in advancing clean energy technologies.